Beneficial Effects of Exercise on Depression and Anxiety During the Covid-19 Pandemic: A Narrative Review - Hu, Shaojuan; Tucker, Lorelei; Wu, Chongyun; Yang, Luodan (Frontiers in Psychiatry, 2020)
First reported in Dec 2019, the on-going COVID-19 pandemic has become a public health emergency of international concern (PHEIC). The isolation and quarantine during the COVID-19 pandemic limited the physical and social activities of the population, which contributed to the increased prevalence of mental disorder. Depression and anxiety are the most common mental illnesses conferring a serious impact on individuals' life quality. This review summarizes the mental health consequences of COVID-19, especially for depression and anxiety. Exercise as an intervention for anxiety and depression has been demonstrated in both of the animal studies and human clinical trials. The underlying mechanism including the regulation on the production of brain-derived neurotrophic factor (BDNF), D-β-hydroxybutyrate, synaptic transmission, hypothalamic pituitary adrenal (HPA) axis, tryptophan hydroxylase, GSK3β/β-catenin pathway, neuroinflammation, oxidative stress and PGC-1α1-PPAR axis. In addition, we summarized the exercise strategies to fight against anxiety and depression according to the information from American College of Sports Medicine (ACSM), World Health Organization and recent literatures about physical exercise during COVID-19.